Identifying and Assessing the Risks of Material Misstatement in Mitigating Money Laundry and Terrorism Financing: Applied Study on Brokerage Companies in Jordan - Owais, Walid; Al Dahiyat, Ahmad; Aburisheh, Khaled (Jordan Journal of Business Administration, 2020)
This study aimed to identify the impact of the application of the International Auditing Standard (315) “Identifying and Assessing the Risks of Material Misstatement through Understanding the Entity and Its Environment”, in reducing money laundry and financing of terrorism in brokerage companies.The study relied on descriptive analytical approach which is considered suitable for the study purposes. The population and sample of the study consisted of all certified public accountants (audit companies) of brokerage firms, which were (23) brokerage firms. A questionnaire was developed and distributed to the study sample which was represented by (75) certified accountants. (63) questionnaire forms were retrieved, two were excluded because of incomplete answers. So, the questionnaire forms which were subject to statistical analysis (61).The study revealed that the International Auditing Standard (315) was highly applied in its five dimensions. A high importance of anti-money laundry (AML) and terrorism financing procedures was found. Furthermore, a statistically significant impact of the elements of the international standard 315: (control environment, risk assessment, control activities, information and communication, monitoring) on reducing money laundry and financing of terrorism in financial brokerage companies in Jordan was found.In light of the results, the study presented a set of recommendations, the most important of which is reviewing the internal control and risk management systems at least once a year, while ensuring that the material risks are identified, managed and disclosed.